2020
DOI: 10.1213/xaa.0000000000001287
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained Methemoglobinemia in Coronavirus Disease 2019: A Case Report

Abstract: Methemoglobinemia is a rare disorder of the blood in which there is an increase in methemoglobin, which occurs when hemoglobin is present in the oxidized form. Methemoglobin impairs hemoglobin’s ability to transport oxygen, produces functional anemia, and leads to tissue hypoxia. We report the successful management of a case of refractory hypoxia due to acutely acquired methemoglobinemia in a patient undergoing treatment for coronavirus disease 2019 (COVID-19) pneumonia. The cause of methemoglobinemia in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 11 publications
0
29
0
3
Order By: Relevance
“…The study selection process is shown in Figure 1a. For the case of COHb and COVID-19, 73 articles were retrieved from PubMed (n = 1) and Google Scholar (n = 72), one duplicate was removed and 68 articles were excluded after abstract review, leading to three articles that were finally included in the present study [20,24,25]. The study selection process is shown in Figure 1b…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study selection process is shown in Figure 1a. For the case of COHb and COVID-19, 73 articles were retrieved from PubMed (n = 1) and Google Scholar (n = 72), one duplicate was removed and 68 articles were excluded after abstract review, leading to three articles that were finally included in the present study [20,24,25]. The study selection process is shown in Figure 1b…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Based on the inclusion and exclusion criteria, seven duplicates were removed and 187 articles were excluded after abstract review. After the full set of remaining articles was screened, seven reports were finally included in the present study [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The study selection process is shown in Figure 1 a.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations